PERAN BUMDES DALAM PENGEMBANGAN DESA WISATA BAHARI TLOCOR SIDOARJO - Shalenia Anggi Christy; Hardjati, Susi (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2025)
Tlocor Maritime Tourism Village is one of the tourism potentials being developed in Sidoarjo Regency. In its development, Kedungpandan Village-Owned Enterprise (BUMDES) has an important role in managing and mobilizing community participation. This study aims to analyze the role of BUMDES in the development of tourist villages using three indicators, namely: conscientization, community organizing, and resources delivery. The approach used in this research is descriptive qualitative. Data collection techniques were conducted through interviews, observation, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing.The results showed that in the aspect of awareness, BUMDES has attempted to raise community awareness of tourism potential through socialization and direct involvement. In the aspect of community organizing, BUMDES forms a systematic business unit structure and involves residents in operational management. Meanwhile, in the aspect of human resource delivery, BUMDES creates jobs and organizes training, although it is not yet comprehensive for all business actors. Constraints include the lack of income stability for workers and limited technical training. Nonetheless, the role of BUMDES in tourism village development has contributed significantly to economic independence and increased community participation.